2013
DOI: 10.1182/blood-2012-06-434100
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance induction with gene-modified stem cells and immune-preserving conditioning in primed mice: restricting antigen to differentiated antigen-presenting cells permits efficacy

Abstract: Key Points• Restricting transgenic antigen expression to differentiated antigen-presenting cells protects hematopoietic progenitors from immune attack.• Restricting transgenic antigen expression to differentiated antigen-presenting cells promotes tolerogenic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(60 citation statements)
references
References 48 publications
(86 reference statements)
4
56
0
Order By: Relevance
“…Donor-type leukocyte accumulation, indicating engraftment, was lower in HSPC than BM recipients (Fig. 4A), as anticipated from previous studies (22). However, 5 weeks after HSPC or BM transfer, total spleen cell number did not differ between groups (Fig.…”
Section: Tmem Inactivation Requires Engraftment Of Antigenencoding Hesupporting
confidence: 73%
See 2 more Smart Citations
“…Donor-type leukocyte accumulation, indicating engraftment, was lower in HSPC than BM recipients (Fig. 4A), as anticipated from previous studies (22). However, 5 weeks after HSPC or BM transfer, total spleen cell number did not differ between groups (Fig.…”
Section: Tmem Inactivation Requires Engraftment Of Antigenencoding Hesupporting
confidence: 73%
“…We now advance this to show application to the clinical challenge of b-cell-specific memory T-cell responses that represent a strong impediment to islet graft survival. Previous studies showed when using gene-modified BM transfer that restricting antigen expression to differentiated APCs permitted BM engraftment under immune-preserving conditions in naive and primed recipients (22). However, the fate of established memory T cells was not examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of antigens in APC, including DCs, induces T cell tolerance and prevents antigen-specific T cell responses under classical Th1-inducing conditions (23,27). To test this potential under Th2-inducing conditions, mice expressing OVA in DC (DC.OVA) and nontransgenic (non-Tg) controls were i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Transfer of antigen-encoding BM or hematopoietic stem and progenitor cells (HSPC) using mild conditioning transfers a tolerogenic environment to hosts (27) and has therapeutic potential (28). Here, we sought to determine whether this could terminate pathogenic Th2 responses in an allergic airways disease (AAD) setting.…”
Section: Introductionmentioning
confidence: 99%